Does One Health need an ontological turn? - Andrea Kaiser-Grolimund; Salome A. Bukachi; Julia Karuga; Laura Kämpfen; Frédéric Keck; Jakob Zinsstag; Hannah Brown (Critical Public Health)
One Health has gained global prominence in recent years. Alongside its emergence, there have been extensive social science critiques. In this contribution, we make the case for the value of recent theoretical discussions in the field of anthropology – sometimes referred to as an ‘ontological turn’. We argue that taking theory seriously benefits One Health as an integrated approach that has interdisciplinary collaborations at its heart, but which encounters challenges when conversations based on different epistemological and ontological positions result in voices talking past each other. In this contribution, we offer two examples of what One Health specialists can gain from anthropologically-informed ontological thinking. Both require questioning ontological premises. Firstly, questioning assumptions about distinctions between animals and humans. Secondly, questioning the universality of biomedical knowledge. In the conclusion, we underline the importance of an ontological openness when it comes to the constitution and position of the actors as well as different bodies of knowledge that are involved in One Health and we show that talking to each other with awareness of different ontological positions is not impossible.